2013
DOI: 10.1177/2049463713489539
|View full text |Cite
|
Sign up to set email alerts
|

Acute high-altitude illness: a clinically orientated review

Abstract: Acute high-altitude illness is an encompassing term for the range of pathology that the unacclimatised individual can develop at increased altitude. This includes acute mountain sickness, high-altitude cerebral oedema and high-altitude pulmonary oedema. These conditions represent an increasing clinical problem as more individuals are exposed to the hypobaric hypoxic environment of high altitude for both work and leisure. In this review of acute high-altitude illness, the epidemiology, risk factors and pathophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 52 publications
0
25
0
7
Order By: Relevance
“…For example, long-term exposures to an altitude above 4 km could induce a loss of appetite, leading to nutrition deficiency and weight loss (Siesjö et al, 1996; Wasse et al, 2012). Collectively, these symptoms associated with acute mountain sickness are related to harsh environmental factors such as low oxygen, cold, and ultraviolet rays (Askew, 2002; Smedley and Grocott, 2013). Particularly, hypobaric hypoxia generates a large amount of ROS, resulting in the subsequent tissue injuries in mountaineers (Askew, 2002; Julian et al, 2014).…”
Section: Ros Generation In Various Types Of Exercisementioning
confidence: 99%
“…For example, long-term exposures to an altitude above 4 km could induce a loss of appetite, leading to nutrition deficiency and weight loss (Siesjö et al, 1996; Wasse et al, 2012). Collectively, these symptoms associated with acute mountain sickness are related to harsh environmental factors such as low oxygen, cold, and ultraviolet rays (Askew, 2002; Smedley and Grocott, 2013). Particularly, hypobaric hypoxia generates a large amount of ROS, resulting in the subsequent tissue injuries in mountaineers (Askew, 2002; Julian et al, 2014).…”
Section: Ros Generation In Various Types Of Exercisementioning
confidence: 99%
“…Cough that is dry at onset and expectorant with pink frothy sputum later is also very common accompaniment. Only 50 per cent of HAPE patients have concurrent AMS and 14 Per cent have concurrent HACE 18 , while 5 Per cent of autopsies of fatal HAPE have evidence of cerebral oedema 28 .…”
Section: Referencesmentioning
confidence: 99%
“…Maximum altitude gained too influences the likelihood of AHAI-AMS typically develops at altitudes>2,500, HAPO at > 3000 m and HACO between 4000 m -5000 m 18 . A large body of evidence points towards individual susceptibility as an interactive outcome between: genetic and environmental factors 18,19 . Studies on Tibetan and Andean populations have revealed different genetic phenotypes 20 .…”
Section: Epidemiology and Riskmentioning
confidence: 99%
“…Textinn byggist á helstu heimildum sem fundust á PubMED, MEDLINE og í heimildaskrám nýlegra yfirlitsgreina. [5][6][7][8][9] Fyrst er fjallað um eðlilega haeðaraðlögun og lífeðlisfraeði hennar en síðan greint frá birtingarmyndum og meinlífeðlisfraeði þeirra sjúkdóma sem geta gert vart við sig í mikilli haeð. Loks er útskýrt hvernig fyrirbyggja má haeðarveiki og meðhöndla.…”
Section: á G R I Punclassified